2018
DOI: 10.14302/issn.2577-2279.ijha-18-2384
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Rats’ Liver Structure Induced by Zinc Oxide Nanoparticles and the Possible Protective Role of Vitamin E

Abstract: Background: Oral ingestion of zinc oxide nanoparticles (ZnONPs) may lead to serious liver injury. Vitamin E (VE) is an important antioxidant factor that can reduce such damage. Aim: This study aimed to evaluate the possible changes that could take place in the liver of adult male albino rats after oral ingestion of ZnONPs and elucidate the potential protective role of VE against such damage. Material and Methods: Forty eight male albino rats were divided into four groups of 12 animals each. Group (1) served as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
2
8
1
Order By: Relevance
“…In addition, Mansouri et al (2015) reported that injection with ZnO NPs induced a significant increase in oxidative stress through the increase in lipid peroxidation (malondialdehyde (MDA)) accompanied with a significant decrease in superoxide dismutase and glutathione peroxidase enzyme activity in the liver tissue. Several studies have reported the toxic effects of ZnO NPs on liver function (Amara et al, 2014; Hegazy et al, 2018; Sharma et al, 2012). Amara et al (2014) investigated the possible toxic effect of combined injection of ZnO NPs and ZnCl 2 solution in rats, and they related this effect to Zn + ion release and accumulation of this element in liver and kidney tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Mansouri et al (2015) reported that injection with ZnO NPs induced a significant increase in oxidative stress through the increase in lipid peroxidation (malondialdehyde (MDA)) accompanied with a significant decrease in superoxide dismutase and glutathione peroxidase enzyme activity in the liver tissue. Several studies have reported the toxic effects of ZnO NPs on liver function (Amara et al, 2014; Hegazy et al, 2018; Sharma et al, 2012). Amara et al (2014) investigated the possible toxic effect of combined injection of ZnO NPs and ZnCl 2 solution in rats, and they related this effect to Zn + ion release and accumulation of this element in liver and kidney tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated the male rats to avoid the effect of hormonal changes of oestrus cycles of females 21 that showed weight loss in tumour bearing rats 25 . They also showed that this is mediated by TNF.…”
Section: Discussionmentioning
confidence: 99%
“…Cholestatic injury may be considered as another possible mechanism for Deferasirox-induced liver injury [39]. The drug may block bile salt transport proteins in the canalicular membranes responsible for the generation of bile.…”
Section: Alt Ast Enzymes and Histopathologic Changes Induced By Concanavalin A [36]mentioning
confidence: 99%